Modalitas Bahasa Jepang dalam Kalimat Berpola ~To Omou - Irma Winingsih (Japanese Research on Linguistics, Literature, and Culture, 2020)
This writing uses a syntactic study to analyze modality to analyze the sentence structure of verb phrases ~ to omou 'my taste/thought/intention'. From the data the author analyzes, the modality found is the modality of ganbou's' intention', the modality of gaigen 'possibility/uncertainty' and the modality of kakugen 'full of confidence statementâ€™. Â In a sentence it is possible to find two modalities, as in the data above which gives rise to two modalities, namely toui and gaigen modalities, while in other sentences it contains ganbou and gaigen modalities.